2018
DOI: 10.1016/j.ymben.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of photoautotrophic carbon flux topology in Synechocystis PCC 6803 using genome-scale carbon mapping models

Abstract: Completeness and accuracy of metabolic mapping models impacts the reliability of flux estimation in photoautotrophic systems. In this study, metabolic fluxes under photoautotrophic growth conditions in the widely-used cyanobacterium Synechocystis PCC 6803 are quantified by re-analyzing an existing dataset using genome-scale isotopic instationary C-Metabolic Flux Analysis (INST-MFA). The reconstructed carbon mapping model imSyn617 and implemented algorithmic updates afforded an approximately 48% reduction in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
152
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(153 citation statements)
references
References 69 publications
0
152
1
Order By: Relevance
“…Here, data revealed instances of both rigidity and plasticity in Synechocystis central carbon metabolism. For example, the production of pyruvate in Synechocystis has been predicted to be mainly through decarboxylation of oxaloacetate by NADPdependent malic enzyme, not dephosphorylation of phosphoenolpyruvate by pyruvate kinase 18 . However, malic enzyme (me, slr0721) and pyruvate kinase (pyk2, sll1275) both have low fitness scores ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, data revealed instances of both rigidity and plasticity in Synechocystis central carbon metabolism. For example, the production of pyruvate in Synechocystis has been predicted to be mainly through decarboxylation of oxaloacetate by NADPdependent malic enzyme, not dephosphorylation of phosphoenolpyruvate by pyruvate kinase 18 . However, malic enzyme (me, slr0721) and pyruvate kinase (pyk2, sll1275) both have low fitness scores ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, reaction lumping restricted the metabolite-labeling dynamics afforded by a core model, leading to significant disagreements between experimentally measured labeling dynamics and those predicted using simplified models (Nöh and Wiechert, 2011). In order to mitigate the effect of these factors on the accuracy of flux estimation, the scope of the INST-MFA technique has been expanded to genome-scale models with the implementation of an efficient algorithm for the simulation of metabolitelabeling dynamics (Gopalakrishnan et al, 2018). Meta-analysis of the labeling dynamics observed under photoautotrophic conditions in Synechocystis sp.…”
mentioning
confidence: 99%
“…Meta-analysis of the labeling dynamics observed under photoautotrophic conditions in Synechocystis sp. PCC 6803 (Synechocystis 6803) using genome-scale INST-MFA showed that the genome-scale mapping model (GSMM), namely imSyn617, fitted the experimental data better than the core model (Gopalakrishnan et al, 2018). Interestingly, the flux distribution obtained using imSyn617 was qualitatively different from the one obtained using the core model, as indicated by the reliance on transaldolase (TAL) for the synthesis of Fructose-6-Phosphate (f6p), a bifurcated photorespiratory C2 cycle, and off-gassing of fixed CO 2 by anabolic reactions outside core metabolism.…”
mentioning
confidence: 99%
“…A recent review examines the current status and broad applications of GSMs 38 . In addition, the use of stable isotope labels (i.e., 13 C‐metabolic flux analysis [MFA], 13 C‐MFA) has extensively been used in conjunction with GSMs to ascertain internal metabolic fluxes in both microbial 52,53 and eukaryotic 54 systems. These require not only a metabolic model but also atom mapping models that describe the origin and destination of carbons from reactants to products, 55 as indicated in Figure 2b.…”
Section: Genome‐scale Metabolic Modelsmentioning
confidence: 99%